SIKAP MURID DAN PENJUAL MAKANAN JAJANANTENTANG HIGIENE DAN SANITASI MAKANAN DI SEKOLAH DASAR NEGERI KELURAHAN RONGTENGAH KECAMATAN SAMPANG - Sisca Yanuar Ningtyas; Cahyo Indarto; Banun Diyah Probowati (AGROINTEK, 2012)
Snack foodsplays a fairlyimportant role inprovidingenergyandnutritionalintakefor childrenof school age. Contributionsto theconsumption ofsnackfoodsof school ageaccounted for5.5% and4.2% proteinenergy. Snackfoodsin addition to havingthese advantages, hawkerfoodwasstillrisk to healthbecausetreatmentis oftennotpossiblehygienicsnackfoodcontaminatedbytoxicmicrobes. The purposeofthis studywas to determine theattitudesof studentsandsnackfood vendorsonhygieneandsanitationin the. This type of researchbeinga descriptivestudy sitesat theRongtengah Elementary School, Sampang District. The populationin this study wereelementary school studentsgrades 4, 5and6 dengansample size77 childrenof elementary school students and thenumber of samplesnack food  vendorstotaling10 people. Survey results revealedthat theattitudesof elementary school studentsabouthygieneandsanitationindividuals includedineither categoryat71.43%, while theattitude ofsnackfood vendorsonfoodhygieneandsanitation, including the category of beingas much as 80%.